Safety, Security and Risk Management in Tourism - Velan Kunjuraman, (2021)
Tourism is acknowledged as a business activity and many developed and developing countries are keen to invest in this area. With academic evidences presented by scholars around the world, tourism is no longer a ‘stranger’ to any countries due to the fact that it may provide massive benefits economically. As a result, it is a positive perception by the proponents of tourism comprising of practitioners, government agencies, and the industry to pay attention to this niche area for profit and development objectives. However, the sustainability of tourism is still questionable and possible solutions are needed to overcome the negative impacts of tourism to the environment and welfare of the community. Tourism is a ‘fragile industry’ and often encounters many ‘unwelcomed’ events which cause the image of a country in jeopardy. The reputation of a country is often measured by how safe the country is to be visited by tourists. Such question raises numerous concerns among the academic community and ‘safety and security’ becomes a buzzword for them to motivate empirical studies in this field.With this in mind, the editor is motivated to gather empirical, conceptual, and review papers from scholars who have worked and expertise in the field of safety, security, and risk management in tourism. A total of eleven chapters are devoted to focus on the theme of safety, security, and risk management in tourism with interesting findings are presented by the contributors. All chapters presented in this book are unique and provide an opportunity for the readers to understand the issues, trends, and latest information pertaining to the theme of safety and security in tourism. Moreover, limited academic books in the field of safety and security in tourism is another motivation for the editor to embark in this edited book project. In doing so, this edited book may enhance and enrich the body of knowledge related to the safety and security in tourism as well as serving as a main reference for future researchers to conduct more research and extensive studies within the area.